2017
DOI: 10.3906/sag-1504-28
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of mice gut microflora following oral consumption ofLactobacillus acidophilus and Bifidobacterium bifidum probiotics

Abstract: Background/aim: Thirty male BALB/c mice were equally divided into three groups: control, L. acidophilus, and B. bifidum for the assessment of the probiotics' stability in the gut microflora.Materials and methods: First, the gut microflora of the mice was checked every 3 days (days 3, 6, 9, and 12) without probiotic consumption, and then the mice were daily given orally 1.5 g of probiotics in 30 cc of drinking water. The consumption of probiotics was then stopped for recovery and then the consumption continued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…The inhibition zone diameter against C. albicans ATCC 10231 was 14.5±0.36 mm (15.0±0.0 mm, and 14.50±0.71 mm), which was the lowest ZOI (Table 3). The result of this experiment suggested that the Numerous earlier researches had demonstrated how the three probiotics (Source-1) can coexist and thrive at the same time [35,36,37]. They are the normal flora of the human intestine, and can grow mutually as well as suppress pathogens in the intestine.…”
Section: Antagonistic Activity Test and Comparisonmentioning
confidence: 81%
“…The inhibition zone diameter against C. albicans ATCC 10231 was 14.5±0.36 mm (15.0±0.0 mm, and 14.50±0.71 mm), which was the lowest ZOI (Table 3). The result of this experiment suggested that the Numerous earlier researches had demonstrated how the three probiotics (Source-1) can coexist and thrive at the same time [35,36,37]. They are the normal flora of the human intestine, and can grow mutually as well as suppress pathogens in the intestine.…”
Section: Antagonistic Activity Test and Comparisonmentioning
confidence: 81%
“…It has excellent tolerance to gastric acidity and bile, optimal intestinal mucosa adherence, and pathogen inhibitory actions, and favors immunological responses [ 19 ]. L. acidophilus shows greater stability than B. bifidum in the intestinal microflora of mice in the long-term (5 months) [ 20 ]. PRO with lactobacillus and bifidobacterium has a long history of safety [ 21 ].…”
Section: Introductionmentioning
confidence: 99%